Assisting the rehabilitation by hi-tech - Mateusz Tomanek; Daria Pałucka (Kazimierz Wielki University, 2017)
High-tech, which the use is becoming increasingly popular in medicine, media and education has several advantages as increasing the number of persons to whom these services can hit. Example of such activities is the use of videoconference during rehabilitation, where patients perform basic exercises at home, and physiotherapist could control the movement by on-line video. The use of modern technology is only assisting the rehabilitation, rather than a complete replacement. As the purpose of the article was adopted to show the range of possibilities for the use of high-tech in rehabilitation.